Correction of potassium deficiency in soybean and corn production in southeast Kansas - Matz, Jason D. (Kansas State University, 2012)
Over the last decade low (< 130 mg kg -1) soil test potassium (K) levels and increased crop K deficiency have become a major concern in the clay-pan soils of southeast Kansas. The use of more intense crop rotations and the increased production of high K extracting crops (e.g. soybeans (Glycine max L.)) has significantly increased K removal from these soils. In addition, the traditional use of the nutrient sufficiency-based fertilizer recommendations has resulted in K application rates being substantially lower than removal rates. Because of these practices, many soils that had naturally elevated K availability 25 years ago have declined in K content. More troubling is the extreme yearly variation of soil test exchangeable K levels reported in the region, which has many producers and consultants concerned about proper K management. This study was initiated to examine the extent of K soil test variation and to determine if the variability is impacting plant K availability by analyzing soybean leaf K content and crop yield. A major objective of our research is to identify the mechanism(s) driving these changes in soil test K levels and K availability to crops during the growing season. The long-term goal is to be able to design a soil sampling system and develop alternative K fertilizer recommendation strategies that could alleviate K deficiency impacts on crop yield. Evaluation of different K fertilizer application practices including rate of application and broadcast or surface band methods of application were studied as tools to correct soybean K deficiency. The direct and residual impacts of K fertilization and placement were also evaluated on corn (Zea mays L.) grown in the rotation with the soybeans. Results observed from this research showed that monthly soil samples taken during three crop years at multiple locations have ammonium acetate exchangeable K levels that indeed change dramatically. The data we collected together with data accumulated by farmers and crop consultants showed significant fluctuation in exchangeable K levels of up to 50% on a yearly and even on a monthly basis. Levels seem to demonstrate seasonal changes: higher in the spring months and then decline in the summer and fall. Potassium soil test levels also appear to follow a similar trend as monthly precipitation and soil moisture status. During wet months soil levels tend to increase and then decline during drier months, however, this is not a perfect relationship and other factors are likely to be involved in regulating soil test K levels. No clear effect of K fertilization or method of placement on soybean or corn yields was observed during the study. However, soybean leaf samples revealed that on very low (< 90 mg kg -1) soil test sites surface band applied fertilizer increased leaf K concentrations compared to broadcasted applications. Furthermore, the corn study revealed no distinct difference between using a split annual or biannual fertilizer application system. Maintaining soil test K levels above 130 mg kg -1 using a spring soil test appears to be a successful strategy for avoiding K deficiency. Traditionally most soil sampling occurs in late summer or fall when soil conditions are dry. Our data has demonstrated that during this period one should expect to encounter low soil test results that may not be true indicators of soil K levels during the spring planting months. With that said, spring soil sampling can be difficult to do in a timely fashion due to weather, as well as potential labor restrictions. Another critical point is to not switch back and forth between spring and fall sampling dates. Staying consistent with your sample timing will minimize the seasonal variability that is frequently experienced. Additionally, adopting a build and maintain fertilizer recommendation philosophy rather than a nutrient sufficiency-based recommendation approach is a better nutrient budgeting method to avoid having removal rates exceeding nutrient additions. The best K management proposal would be to consider using a build and maintain approach in combination with basing fertilizer rates on spring soil test K levels.
Keywords: Soil test potassium; Corn potassium fertilization response; Soybean potassium fertilization response; Agronomy (0285)